2021
DOI: 10.1038/s41598-021-97370-9
|View full text |Cite
|
Sign up to set email alerts
|

Virtual and augmented reality in the vestibular rehabilitation of peripheral vestibular disorders: systematic review and meta-analysis

Abstract: Vestibular rehabilitation therapy is an established treatment for patients with vestibular dysfunction. Virtual reality (VR) and augmented reality (AR) can be utilised in vestibular rehabilitation. Evidence of the efficacy of VR and AR delivered rehabilitation in patients with peripheral vestibular disorders is reviewed. MEDLINE, EMBASE, CENTRAL, CINAHL, PsychInfo, PsychBITE, OTSeeker, Ei Compendex, IEE, Clinical trials.gov and WebofScience databases were searched. Reduction in vestibular dysfunction symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 51 publications
0
34
0
5
Order By: Relevance
“…A number of research studies have examined the potential for modern physical therapy technology for the assessment and treatment of patients with vestibular rehabilitation such as virtual reality to improve gaze stability during head movements ( Xie et al, 2021 ), smartphone application for guiding and monitoring exercises ( Moral-Munoz et al, 2021 ), force plateform to measure postural sway ( Song, 2019 ). Moreover, studies report that the management of patients with vestibular dysfunction with evidence-based medicine augmented by advanced therapeutic exercise led to better patient outcomes ( Heffernan, Abdelmalek & Nunez, 2021 ; Xie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of research studies have examined the potential for modern physical therapy technology for the assessment and treatment of patients with vestibular rehabilitation such as virtual reality to improve gaze stability during head movements ( Xie et al, 2021 ), smartphone application for guiding and monitoring exercises ( Moral-Munoz et al, 2021 ), force plateform to measure postural sway ( Song, 2019 ). Moreover, studies report that the management of patients with vestibular dysfunction with evidence-based medicine augmented by advanced therapeutic exercise led to better patient outcomes ( Heffernan, Abdelmalek & Nunez, 2021 ; Xie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality (VR) is an important contribution of computer technology to the vestibular field in recent years. VR is a computer-generated simulation of a visual environment or an activity [16] and is defined as the user entering an interactive environment that mimics reality [17]. At the same time, VR can be defined as using computer technology to create simulations of objects, space, and events.…”
Section: Vestibular Rehabilitation Methodsmentioning
confidence: 99%
“…Head-mounted VE systems are very effective in improving vestibulo-ocular reflex, oculomotor movements, eye tracking, and head-eye coordination. Systems that cannot be integrated with any platform, requiring only eye or head movements or staying still, can be called "passive VR rehabilitation systems," systems that require providing or maintaining postural balance on a moving floor, stepping on a stable floor, walking on a treadmill or doing yoga can be called "active VR rehabilitation systems" [11,15,17,19].…”
Section: Vestibular Rehabilitation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technologies are being applied only to certain diseases in hearing loss, tinnitus, and vestibular disease. Although some studies have reported the efficacy and/or effectiveness of recent technologies especially for VR in otology by using the systematic review [18][19][20] and meta-analysis [3,6], most have been either inconclusive or lack enough topic diversity and/or subjective evidence and do not report any statistical significance. By using a systematic review and a meta-analysis approach, we sought to identify the VR technology applied to hearing loss, vestibular dysfunction, and tinnitus, indeed the representative diseases in the fields of otology and audiology.…”
Section: Introductionmentioning
confidence: 99%